Oyster farming potential in Sabah, Malaysia - Admodisastro, V.A.; Julian Ransangan; N., Ilias; Tan, S.H. (Greenwave Publishing of Canada, 2021)
As the world population increases, demand for food is also on rise. In Malaysia, especially in Sabah, demand for seafood continues to rise due tourism booming and better local living standard. As Malaysia is slowly moving to aquaculture for food security, oyster farming is seen to have high potential to ensure food security and to sustain livelihood of coastal community. In collaboration between Universiti Sains Malaysia (USM) and Universiti Malaysia Sabah (UMS), Income Generation through Oyster Farming programme was introduced in Sabah. This programme is based on the low cost and simple technology required for oyster farming to eradicate poverty and to promote sustainable income generating activities that can be applied by local communities. Two locations within the Tuaran district were selected for this programme. The oyster farming has been proven successful with the community. Hence, this programme does not only address the issues of food security and environmental protection but it fits ideally in the Blue Economy for three pillars of sustainability, the people, planet and profit.